Gene cloning, selection of plasmids and application of Fasciola hepatica cathepsin L1 gene - Kuk, Salih; Erensoy, Ahmet (My University, 2008)
Gene cloning refers to the process by which a fragment of DNA is transferred from one organism to a vector. A vector is an agent that can carry a DNA fragment into a host cell. Commonly used vectors include plasmids, lambda phage, cosmid and yeast artificial chromosome (YAC). Plasmid vectors that have been extensively used in genetic engineering are derived from natural plasmids. These contain a genetic marker conferring a phenotype that can be selected for or against and a polylinker or multiple cloning site (MCS), which is a short region containing several commonly used restriction sites allowing the insertion of DNA fragments at this location easily. There are several plasmids and gene cloning kits available nowadays commercially. These kits contain an advanced positive selection system for the highest efficiency cloning of PCR products generated with any DNA polymerase. The kits offer cloning efficiencies of up to 100% positive clones, eliminating the need for tedious colony screening. We consider that researchers should choose the most suitable plasmids and cloning kits for gene cloning in view of factors such as time consumption, cost and individual laboratory options.
Gen Klonlama, Plazmit Seçimi ve Fasciola hepatica Cathepsin L1 Uygulamalari.
Keywords: Animals; Cathepsins; Cloning, Molecular; Fasciola hepatica; Genetic Vectors; Plasmids; Reagent Kits, Diagnostic; cathepsin; cathepsin L1, Fasciola hepatica; diagnostic agent; unclassified drug; analytical equipment; animal; article; enzymology; Fasciola hepatica; gene vector; genetics; methodology; molecular cloning; plasmid; standard